2015
DOI: 10.2166/wst.2015.507
|View full text |Cite
|
Sign up to set email alerts
|

Tylosin effect on methanogenesis in an anaerobic biomass from swine wastewater treatment

Abstract: The effect of different concentrations of tylosin on methane production was investigated: first methanogenesis in a biomass without contact with the antibiotic, and later the ability of the sludge to adapt to increasing concentrations of tylosin. Results showed that, for biomass that had no contact with the antibiotic, the presence of tylosin inhibits the generation of methane even at concentrations as small as 0.01 mg L(-1), and samples at concentrations above 0.5 mg L(-1) produced practically no methane, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In general, the preponderance of the literature [49,55,74,96,[101][102][103][104][105][106][107][108][109][110][111][112][113] focuses on the effects of antibiotics on the anaerobic digestion process rather than the fate of antibiotics during treatment. Individual antibiotics demonstrate a range of impacts on biogas production, from no effect to complete inhibition.…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…In general, the preponderance of the literature [49,55,74,96,[101][102][103][104][105][106][107][108][109][110][111][112][113] focuses on the effects of antibiotics on the anaerobic digestion process rather than the fate of antibiotics during treatment. Individual antibiotics demonstrate a range of impacts on biogas production, from no effect to complete inhibition.…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…The microorganisms had not only developed resistance to the antibiotics, but also the ability to metabolize them (García-Sánchez et al, 2016). Huang et al (2014a) and Huang et al (2014b) investigated the effects of different antibiotic addition methods (added antibiotics to reactor directly/ added the polluted pig manure to reactor) on methane production from the anaerobic digestion of swine wastes.…”
Section: Anaerobic Digestion (Ad) Processesmentioning
confidence: 99%
“…Chelliapan et al (2011) showed an adaption of methanogens to tylosin, where archaeal cells were not inhibited by tylosin at the concentrations between 100 and 400 mg/L and dominated the reactor. Especially, methanogenesis was not inhibited in the digesters acclimated with 0.01 to 0.065 mg/L tylosin, and methane production was increased (Garcia-Sanchez et al, 2016). It could be inferred that not only the resistance but also the metabolizing ability to antibiotics were developed by such microorganisms.…”
Section: Effects Of Antibiotics On Methanogenic Archaeamentioning
confidence: 92%
“…Adaptation may also occur. Indeed, a low concentration of tylosin, 0.01 mg/L was enough to inhibit methane production for biomass that has not been previously in contact with tylosin; whereas no inhibition of methanogenesis was observed in digesters acclimated with 0.01-0.065 mg/L of tylosin (Garcia-Sanchez et al, 2016). Overall, macrolides decrease methane production by about 10-100% depending on the antibiotic concentration (Table 3).…”
Section: Macrolidesmentioning
confidence: 98%